Enhancing older people's activity and participation with socially assistive robots: a multicentre quasi-experimental study using the ICF framework*. (17th November 2018) - Obayashi, Kazuko; Kodate, Naonori; Masuyama, Shigeru
ABSTRACT: Socially assistive robots (SARs) are seen as part of a pragmatic solution to addressing the increasing demands, shortage of care workers and to realizing the potential of optimum integrated care. Yet their effectiveness and impact on older people's care, activities and participation are still unknown. A total of 67 people aged 65 and over participated in a 24-week-long, quasi-experimental study in five residential nursing homes in Japan. The personalized care plan and targets were created based on the framework of the WHO's International Classification of Function, Disability and Health (ICF). Three types of socially assistive robots were used. The participants in the robot intervention groups showed greater improvements in their scores for targeted activities and participation than the control group. Statistically significant improvements were observed in communication, self care, and social life. SARs have great potential for improving older people's quality of life. With further research, the use of these robots by older people could be considered as a serious option in the future. In addition, the ICF framework can be utilized further for measuring the effects of introducing SARs on older people's quality of life. GRAPHICAL ABSTRACT: